Rekayasa Genetika Pada Tanaman Ditinjau Dari Persepektif Etika - Palit, Bebby Sesilia Laviola (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2024)
Genetic engineering is one of the methods used in biotechnology to modify genes in a living being, in order to achieve a desired purpose. This practice has not only a good impact on human life, but also has a negative impact. The positive impact that can be felt is that GMO plants provide an increase in the quantity and quality of the crops. While the negative impacts appear in the form of threatened survival of conventional plants, the disappearance of uniqueness from plant diversity, and even the shift of the main goal, which is to meet human food needs, to be for personal benefit or for certain groups only. These negative impacts present ethical issues that need to be discussed because they are related to the survival of nature, including humans and plants. This problem will be discussed in this article with a focus on ethical issues that arise from the practice of genetic engineering in plants. Departing from these problems, it will then show the attitudes that can be taken by humans when dealing with these problems. The starting point of these attitudes is the environmental theory of biocentrism and also the accompanying principles.